Wave transport past slotted barriers - Lim, Boon Mo. (2009)
Slotted, vertical wall breakwaters had been increasingly used for coastal protection and harbor creation. Numerous studies had been done on wave interaction with such a barrier. In this project, the focus was on a less researched wave form, solitary wave, and its interaction with the barrier. Wave behavior through the barrier raised several aspect of consideration in the design of the breakwater. Wave energy dissipation and velocity amplification were 2 major components of which implications had to be fully understood. The main interest in this paper was the phenomena of velocity amplification within the gap, as this had implications on local mass transport and seabed scouring. Velocity amplification was established to be correlated to the gap width of the slots and the wave conditions. Through this project, the wave behavior was experimentally simulated on a small scale, and thus provided data for analysis. Theoretical models and equations were also used to give a reference for comparison to observe the effect of amplification. Analysis of theoretical models would also yield predictions and justification of data trends in the experiments. From the data trends observed and through analysis, it was hoped that a definitive correlation model between velocity amplification and various parameters (such as barrier width ratio, and wave height to water depth ratio) could be derived. This would further require the establishment of correlation to be through purely dimensionless parameters, for the purpose of scaling. The observed velocity trends could be further used to study design implications, and investigate the corresponding effects on incipient motion of seabed sediments. The velocity effect on sediment transport was significant, as the main consideration of velocity amplification was its influence on foundation erosion. With this report, it was aimed that more understanding could be achieved on the above various aspects of solitary wave and a model could be formulated for further studies.